Religious Humanism among the Yoruba of Nigeria - Opeloye, Muhib O. (2014)
There is no gainsaying the fact that the arrival of the acclaimed world religions, namely Islam and Christianity have dealt a great blow to the growth of indigenous religion in view of the loss of most of its adherents to the new faiths. This is why the present day Nigerian governments are doing everything possible to revitalize the indigenous culture. It is pertinent to say that even though the Yoruba are today mostly Muslims and Christians, they still practise their religions within the context of their indigenous cultural background. The diversity in religious beliefs of the Yoruba shows that the people have wider religious experience. This article is therefore concerned with the religious aspect of the Yoruba culture. We shall examine the basic beliefs and practices of the three main religions practised in Yorubaland with a view to high-lighting their impact on their life.